Smart world cities in the 21st century. - Mainka, Agnes (De Gruyter Saur, 2018)
The term smart city has become a buzzword. City planners develop ubiquitous connectivity through Wi-Fi hotspots, establish science parks, introduce bike and car sharing, and push entrepreneurship. All this is happening under the flagship of becoming a knowledge city. This book investigates the digital and cognitive infrastructure of 31 cities and how they meet the demands of the knowledge society in an increasingly digitized environment.
Keywords: Stadtplanung; Stadtsoziologie; Information; Informationstechnologie; Weltstadt; Smart City; Informationsgesellschaft; Stadtsystem; Digitalisierung; Datenverwendung; Wissen; Städtevergleich